Selective photocatalytic CO2 reduction on copper–titanium dioxide: a study of the relationship between CO production and H2 suppression. Issue 56 (13th June 2019) - Lan, Yangchun; Xie, Yongzhi; Chen, Jiaxi; Hu, Zhuofeng; Cui, Dehu
Abstract : High selectivity of CO2 reduction and suppression of H2 evolution on a Cu/TiO2 photocatalyst. Abstract : Low selectivity and the competing reaction of hydrogen evolution are two problems in photocatalytic CO2 reduction. Herein, we deposited highly crystalline metallic Cu nanoparticles onto TiO2 photocatalysts using a solvothermal method. They were found to convert CO2 into CO without any by-products. Importantly, hydrogen evolution can be suppressed after a reaction time of 1–2 h with a high generation rate and selectivity for CO production.